Kinetic Models to Produce an Antioxidant by Enzymatic Hydrolysis of Bovine Plasma Protein Using a High Substrate Concentration - Gómez, Nathalia A.; Gómez, Leidy J.; Zapata, José E. (Current Enzyme Inhibition, 2019)
Background: The animal blood that is produced in a slaughterhouse is a potential source of inexpensive proteins used in the food industry around the world. However, 60% of it is surplus, and it ends with a negative environmental impact. Introduction: The enzymatic hydrolysis of proteins represents a good way to produce peptides with different biological activities. Methods: Enzymatic hydrolysis of bovine plasma with subtilisin at an alkaline pH and 61.5°C was performed using the pH-stat method. Experiments were conducted considering the effects of a high initial substrate concentration (So) and the enzyme/substrate ratio (E/S) minimizing the processing time necessary to obtain a specific degree of hydrolysis (DH). Results: The best conditions obtained were 42 g/L of So and 0.89 AU/g substrate of E/S until a DH of 20% in 11,1 ± 1,1 min was achieved to the tested conditions, which result in a fitted empirical polynomial equation of degree 3. Conclusion: A kinetic equation is established to relate the DH and the reaction time to a relative error of less than 5% in the fit, to obtain a good antioxidant product in an industrially interesting time. Additionally, the results suggest a good adjustment of the data with a determination coefficient (R2) of 0.9745 in validation.
Keywords: pH-Stat method